2020
DOI: 10.3389/fmicb.2020.576661
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Distribution of Archaea From Soil to Freshwater to Estuary: Implications of Archaeal Composition and Function in Different Environments

Abstract: Wang et al. Archaeal Distribution Across Distinct Environments network analysis indicated that only soil Archaea formed stable modules. Keystone species (ASVs) were identified mainly from Methanomassiliicoccales, Nitrososphaerales, Nitrosopumilales. Overall, these results indicate a strong habitat-dependent distribution of Archaea and their functional partitions within the local environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 76 publications
0
13
0
Order By: Relevance
“…Yu, Lawrence, Sooksa-nguan, Smith, Tenesaca, Howe, and Hall [56] found that typically Nitrososphaeraceae (F) are AOA and positively associated with pH, but the pH relationship depended on niche specialties of certain archaea. Woesearchaeia (C) and Thermoplasmata (C) Marine Group II are typically found in aquatic ecosystems [112][113][114]. However, Wang et al [115] found both archaea ASVs in agricultural and estuarial soils, noting that the agricultural soils contained significantly greater abundance, richness, evenness, and diversity than freshwater or estuarine ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…Yu, Lawrence, Sooksa-nguan, Smith, Tenesaca, Howe, and Hall [56] found that typically Nitrososphaeraceae (F) are AOA and positively associated with pH, but the pH relationship depended on niche specialties of certain archaea. Woesearchaeia (C) and Thermoplasmata (C) Marine Group II are typically found in aquatic ecosystems [112][113][114]. However, Wang et al [115] found both archaea ASVs in agricultural and estuarial soils, noting that the agricultural soils contained significantly greater abundance, richness, evenness, and diversity than freshwater or estuarine ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, archaeal abundance showed a positive correlation with soil basal respiration, which was a major process that controlled the C loss from terrestrial ecosystem. This result suggested that archaea, instead of bacteria and fungi may play crucial roles in soil C mineralization in urban forests in Shanghai, China (Wang et al., 2020; Yu et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Denitrification of soil by ammonia-oxidizing archaea (AOA) oxidizes nitrite to nitrate. Thaumarchaeota is the largest contributor to ammonium oxidation and one of the most abundant in the planet and easily found in the soil [40][41][42]. Thaumarchaeota is known to live in a wide range of environmental conditions.…”
Section: Bacteriamentioning
confidence: 99%
“…They live in fresh water to oceans, from pH 3.5 to pH 8.7, and from low temperature environment such as Artic to very high temperature environments (between 74 • C to 124 • C) such as hot springs [41]. They receive ammonia from urea and cyanate [42]. However, nitrification process by AOA may also lead to nitrate leaching from soils, causing groundwater and surface contamination with nitrous oxide (N 2 0), resulting in further acceleration of global warming [15].…”
Section: Bacteriamentioning
confidence: 99%